2021
DOI: 10.1007/s11356-021-15902-2
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics analysis of COVID-19 prevention and control strategies

Abstract: The COVID-19 pandemic now affects the entire world and has many major effects on the global economy, environment, health, and society. Focusing on the harm COVID-19 poses for human health and society, this study used system dynamics to establish a prevention and control model that combines material supply, public opinion dissemination, public awareness, scientific and technological research, staggered work shifts, and the warning effect (of law/policy). Causal loop analysis was used to identify interactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In addition, these policies are focused on the general population while people with limited ADL deserved further attention. Meanwhile, relevant studies ( 52 , 53 ) indicated that policies usually had delayed or lag effects. Policies about access to healthcare services usually include comprehensive and complicated issues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these policies are focused on the general population while people with limited ADL deserved further attention. Meanwhile, relevant studies ( 52 , 53 ) indicated that policies usually had delayed or lag effects. Policies about access to healthcare services usually include comprehensive and complicated issues.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two studies covered the topic of infectious disease modelling. System dynamics has also been used to model the transmission of Covid-19 under different policy scenarios ( Feng and Lu, 2020 , Struben, 2020 , Sy et al, 2020 , Jia et al 2022 ). However, relatively few studies using system dynamics to assess the resilience of urban mobility systems in the face of threats, such as Covid-19, were found.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Numerous research studies have revealed a strong correlation between COVID-19 spread and unsustainable conditions with excessive air pollution (Coccia 2020 ). Jia et al ( 2022 ) focused on the harm COVID-19 poses to human health and society. The authors applied system dynamics to create a prevention and control model that incorporated material supply, public opinion dissemination, public awareness, scientific and technological research, staggering work shifts, and warning effect (of law/policy).…”
Section: Introductionmentioning
confidence: 99%